Preminary results of riverstrahler model application to the red river system (Vietnam) - Phuong Quynh et al, Le Thi (Vietnam Journal of Chemistry, 2014)
The Riverstrahler model has been developed for representing the biogeochemical functioning of large drainage networks in Europe. It is originally here applied to a tropical river system, the Red river, a 156 448 km transboundary river system. For this purpose, a GIS data base is being assembled at the scale of the whole basin, with layers documenting geomorphology, lithology, meteorology, land-use and agriculture, population, domestic and industrial wastewater release, etc. The results of the model, although still preliminary, are in agreement with a set of validation discharge and water quality data newly acquired at the outlet of the 4 sub-basins (Da, Lo, Thao and in the main axe) during the year 2002. Some discrepancies are discussed and indicate the need for further research and monitoring.